EFFECTIVENESS OF FEEDBACK MECHANISMS IN CDAs OFFICES AND YOUTH GROUPS:A CASE STUDY OF NYERI TOWN CONSTITUENCY YOUTH ENTERPRISE SCHEME (C-YES), KENYA - Mburu, Jinaro Paul; Ngugi, Dr. Muiru (International Journal of Communication and Public Relation, 2017)
Purpose: The purpose of this study was to establish the effectiveness of Feedback mechanisms in CDAs offices and Youth Groups. Methodology: A descriptive survey research design was used. Questionnaires were used to collect data. A population of 260 respondents was chosen, consisting of 200 youth groups and 60 CDAs. A sample size of 50% was chosen. The sample was 130 individuals divided into 100 youth groups and 30 CDAs. The tool for analysis was S.P.S.S; a Windows based statistical Package for social science. Presentation of the findings was done in tabulated and graphical formats. Results: Findings indicated that the feedback mechanisms between youth groups and CDAs are not effective and this may have a bearing on the successful disbursement of youth funds. This conclusion was reached because both groups disagreed acknowledging the receipt of letters, emails, replying of emails, returning calls left on voice mail and confirmation of attendance or non- attendance to organized meetings. Unique Contribution to Theory, Practice and Policy: Following study results, it was recommended that the stakeholders ensure that both groups have feedback mechanisms that will ensure that there are effective communication channels. The groups should agree on the channels of communication to use for example if they prefer emails, telephone, SMS and social media. Keywords: Feedback mechanisms, CDAs offices and Youth Groups.